2019
DOI: 10.1007/s00406-019-00984-4
|View full text |Cite|
|
Sign up to set email alerts
|

How effective and safe is medical cannabis as a treatment of mental disorders? A systematic review

Abstract: We conducted a review of systematic reviews (SRs) and randomized-controlled trials (RCTs) to analyze efficacy and safety of cannabis-based medication in patients with mental disorders. Five data bases were systematically searched (2006—August 2018); 4 SRs (of 11 RCTs) and 14 RCTs (1629 participants) were included. Diagnoses were: dementia, cannabis and opioid dependence, psychoses/schizophrenia, general social anxiety, posttraumatic stress disorder, anorexia nervosa, attention-deficit hyperactivity disorder, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 85 publications
1
93
0
9
Order By: Relevance
“…The evidence base for the anticonvulsant gabapentin, oxytocin and N‐acetylcysteine is weak. Another systematic review found mixed effects of THC preparations for the reduction of cannabis withdrawal symptoms and treatment retention. A recent randomized controlled trial (RCT) tested the efficacy and safety of the FAAH‐inhibitor PF‐04457845 in male daily cannabis users and found that those who received the drug, compared to placebo, had fewer withdrawal symptoms and used less cannabis 4 weeks later.…”
Section: Clinical Representationmentioning
confidence: 99%
“…The evidence base for the anticonvulsant gabapentin, oxytocin and N‐acetylcysteine is weak. Another systematic review found mixed effects of THC preparations for the reduction of cannabis withdrawal symptoms and treatment retention. A recent randomized controlled trial (RCT) tested the efficacy and safety of the FAAH‐inhibitor PF‐04457845 in male daily cannabis users and found that those who received the drug, compared to placebo, had fewer withdrawal symptoms and used less cannabis 4 weeks later.…”
Section: Clinical Representationmentioning
confidence: 99%
“…One such novel target could be the endocannabinoid (eCB) system. eCBs regulate several central nervous system functions, including motor control, repetitive behaviors, pain perception, anxiety, stress, learning and memory, and social behaviors (7,8), all of which are implicated in ASDs (1). Regarding social behaviors, the eCB 2-arachidonoylglycerol (2-AG) has a demonstrably significant role in regulating social behavior because increasing levels of 2-AG increases social play in juvenile rats, while decreasing 2-AG decreases acquisition of social conditioned place preference (CPP) (9, 10) in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Previous efforts to synthesize the evidence for medical cannabis use in patients with psychiatric disorders have been published (Hoch et al, 2019;Lowe et al, 2019). For example, Hoch et al conducted an excellent systematic review that summarized four systematic reviews and 14 randomized controlled trials (RCTs), but did not consider non-clinical trial evidence (case reports and case series) (Hoch et al, 2019). A review by Mandolini et al recently summarized the clinical findings from 14 studies of psychiatric disorders, but these authors did not provide information about nabiximols (Mandolini et al, 2018).…”
Section: Introductionmentioning
confidence: 99%